Transformation of Social Studies Learning in Early Elementary School Grades in the Independent Curriculum Through the Application of Technology: Increasing Students' Enthusiasm for Learning Towards a Competitive Future - Hanif Khotimah; Sabrina Octaf Erina; Zahra Amanda Koswara; Tin Rustini (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The application of technology in early grade elementary school social studies learning has an unacceptable significance. Digital technology, such as video media and the internet, can help clarify material and make learning more interesting and interactive. This study uses a qualitative descriptive method with data collection techniques through literature studies and compiling data and conclusions. This will help students understand the material better and improve learning outcomes. In addition, the use of technology can also help develop digital literacy and 21st century skills. However, to use technology in effective learning, teachers must have adequate technological literacy and understand how to use technology as a learning tool. In addition, adequate technical support and technological infrastructure must also be available.